Brewing socialism : coffee, East Germans, and 20th century globalization - Kloiber, Andrew 2017- (Studies in German history, 2023)
"Placing coffee at the center of its analysis, Brewing Socialism links East Germany's consumption and food culture to its relationship to the wider world. Andrew Kloiber reveals the ways that everyday cultural practices surrounding coffee drinking not only connected East Germans to a global system of exchange, but also perpetuated a set of traditions and values which fit uneasily into the Socialist Unity Party's conceptualization of a modern Socialist Utopia. Sifting through the relationship between material culture and ideology, this unique work examines the complex tapestry of traditions, history and cultural values that underpinned the socialist German Democratic Republic (GDR)"